Inflation and Public Support for the Euro - Felix Roth (University of Hamburg, Department of Economics, Privatdozentur in Economics, 2026)
The paper finds that the post-pandemic inflation surge and subsequent decline from 2021 to 2024 had no significant impact on public support for the Euro for the EA-19 and for most individual member states of the EA-19. From 2021 to 2024, net public support for the euro remained remarkably stable and reached historically high values across the EA-19. Perceptions of inflation in the national and personal economic situation had no significant effect on public support for the euro during the post-pandemic inflation surge and subsequent decline from 2021 to 2023. These findings contrast with those for the before-crisis and crisis periods, in which inflation and inflation perceptions had a significant negative impact on public support for the euro. Similar to public support for the euro, trust in the institutions that govern the Euro was also not affected by the post-pandemic inflation surge.
Keywords: C32; C33; D84; E31; E42; E52; O52; 330; Inflation; COVID-19; Post-Pandemic Inflation Surge and Decline; Inflation Perception; Public Support for the Euro; Euro Area; Trust in the ECB